2001
DOI: 10.1590/s1516-35982001000800007
|View full text |Cite
|
Sign up to set email alerts
|

Estimativas de Herdabilidade e Correlação Genética para Características de Crescimento na Fase de Pré-desmama e Medidas de Perímetro Escrotal ao Sobreano em Bovinos Angus-Nelore

Abstract: RESUMO -Os dados utilizados neste estudo são originários de 53.938 bovinos puros e cruzados (Angus x Nelore), coletados em várias regiões do Brasil e da Argentina nascidos entre 1987 e 1998. O objetivo do trabalho foi verificar as herdabilidades e as correlações existentes entre as características de crescimento e as medidas de perímetro escrotal (PE). As variáveis estudadas foram ganho médio diário do nascimento à desmama (GMDND), dias para ganhar 160 kg do nascimento à desmama (D160), peso à desmama (PD) e p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
3
2
0
6
Order By: Relevance
“…The magnitude of the heritability estimates for all traits can be considered sufficient to promote substantial genetic gains in the Nelore breed. In this study, the components of variance and heritability estimates obtained for growth traits using single-trait analyses were consistent with analogous values reported in the literature (Gressler et al, 2000;Mercadante et al, 2000;Everling et al, 2001).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The magnitude of the heritability estimates for all traits can be considered sufficient to promote substantial genetic gains in the Nelore breed. In this study, the components of variance and heritability estimates obtained for growth traits using single-trait analyses were consistent with analogous values reported in the literature (Gressler et al, 2000;Mercadante et al, 2000;Everling et al, 2001).…”
Section: Resultssupporting
confidence: 91%
“…Comparing the two methodologies and using Nelore field data, Magnabosco et al (2000) reported that the Gibbs sampling estimates were greater than those obtained by REML, but with similar results to those of other previous studies on Nelore cattle (Mercadante et al, 2000;Everling et al, 2001). Resende (2000) reported that Bayesian inference estimates were more precise than REML estimates, and have the advantage of producing standard deviations and confidence intervals for (co)variance components and genetic parameters as well as the marginal posterior densities.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Esses resultados foram similares aos obtidos por Neser et al (2012). Everling et al (2001) obtiveram valor inferior (0,16) de rg entre P205 e PE. Os valores obtidos mostram a existência de genes que atuam na expressão fenotípica de mais de uma característica, o que indica que a seleção para determinada característica pode resultar em ganho genético em outra.…”
Section: Resultsunclassified
“…As estimativas de herdabilidade de características de crescimento, em rebanhos da raça Brangus, variam de 0,20 (peso ao sobreano) a 0,43 (peso à desmama) (Everling et al, 2001;Lopes et al, 2009;Araújo et al, 2010). Entretanto, no Brasil, são poucos os trabalhos sobre estas estimativas e as de correlações genéticas (Lopes et al, 2009) entre os pesos mensurados em diversas idades, para a raça.…”
Section: Introductionunclassified